2019
DOI: 10.1016/j.ipej.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pulmonary vein reconnection post Cryoballoon ablation

Abstract: Background The Arctic Front Cryoballoon System is a technology in which substrate alterations in patients with atrial fibrillation (AF) recurrence have not been well characterized. In this study, we evaluated sites of pulmonary vein (PV) reconnections and the accuracy of the Achieve™ circular mapping catheter in detecting these reconnections after cryoablation. Methods This study included 15 patients undergoing redo AF ablation after a prior single cryoablation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…In our study PV reconnections after CB PVI were most frequently observed in LSPVs. This finding is consistent with data presented by Shah et al and Glowniak et al [12,16], while Aryana et al found CTs most frequently reconnected after CB PVI [3]. The anatomical ridge between LSPV and LAA, a common reconnection site with increased wall thickness, reduces the creation of a complete transmural lesion and thus may result in frequent reconnections of the left superior PV.…”
Section: Pv Reconnection Patterns After Cb Pvisupporting
confidence: 90%
See 1 more Smart Citation
“…In our study PV reconnections after CB PVI were most frequently observed in LSPVs. This finding is consistent with data presented by Shah et al and Glowniak et al [12,16], while Aryana et al found CTs most frequently reconnected after CB PVI [3]. The anatomical ridge between LSPV and LAA, a common reconnection site with increased wall thickness, reduces the creation of a complete transmural lesion and thus may result in frequent reconnections of the left superior PV.…”
Section: Pv Reconnection Patterns After Cb Pvisupporting
confidence: 90%
“…To distinguish atrial far-field signals from PV potentials, coronary sinus pacing from different sites was performed, if necessary. PVI with verified entrance and exit block or absence of any electrical signal for ≥30 min was performed by the achieve catheter [12].…”
Section: Cryoballoon Pvimentioning
confidence: 99%
“…These results after PVAC PVI indicate that significant PV reconnections must be expected at repeat ablation. In contrast to PVAC PVI, Shah et al found an average PV reconnection rate after CB PVI of 2.1 ± 0.8 PVs/patient, which is comparable with our data of 1.97 ± 0.8 reconnected PVs/patient 10 …”
Section: Discussionsupporting
confidence: 91%
“…After written informed consent, CB ablation was performed under mild conscious sedation, as described previously by our group 10 . A 15‐ or 20‐mm diameter inner lumen catheter (Achieve TM , Medtronic) was placed in each targeted PV to record PV signals before, during and after ablation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation